Pengaruh Media Sosial terhadap Pergeseran Gaya Hidup Remaja Kristen di Mogoynggung - Tita Langi (LPPM STT Baptis Kalvari, 2023)
In the modern era, the development of social media has become a trend that cannot be separated from people's lives, including among Christian teenagers in Mogoyunggung. The use of social media among teenagers can have both positive and negative impacts. One aspect that is influenced by social media in this era is the aspect of social behavior. Teenagers who are in the transition from childhood to adulthood are very vulnerable to negative influences that occur in their social environment and through social media. Almost all members of the community in Mogoyunggung have social media accounts such as Facebook and TikTok. Starting from parents, teenagers, and even 5-year-old children already have a Facebook account. In addition to the influence of social media on the shift in the lifestyle of Christian teenagers, there is also the influence of free association that can affect the lifestyle of Christian teenage children. Teenagers have uncontrolled freedom in accessing social media. Having freedom in accessing social media makes someone not have time to interact with others, but only focuses on accessing social media. This research is a qualitative study using methods to collect data through books, the internet, journals, and interviews. The purpose of this study is to understand the positive and negative impacts on the lifestyle of Christian teenage children in Mogoyunggung. Thus, the results of this study can provide awareness in using time effectively, such as worshiping, praying, and learning.